2014
DOI: 10.14260/jemds/2014/2397
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Dexmedetomidine Propofol v I Rus Fentanyl – Propofol for Conditions of Laryngeal Mask Airway Insertion in Elective Surgeries

Abstract: BACKGROUND: Laryngeal Mask Airway (LMA) is a supraglottic airway device, requiring optimal conditions for insertion to minimize the hemodynamic perturbation associated with LMA insertion. The aim of our study is to compare Dexmedetomidine-Propofol (Dp) and Fentanyl-Propofol (Fp) for conditions of LMA insertion in short surgeries under general anesthesia. AIMS AND OBJECTIVES: To compare efficacy of Dexmedetomidine-Propofol and Fentanyl-Propofol for LMA insertion in terms of 1) Ease of insertion, 2) The Hemodyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The overall insertion condition, as summarized by Lund and Stovener's modified scheme [5], was comparable in both groups (Tables 2 and 3). Our findings are consistent with the findings of Lande et al [9], who compared Dexmedetomidine and Fentanyl for LMA insertion and found that Dexmedetomidine resulted in an absolutely relaxed jaw in 96.6% of patients.…”
Section: Discussionsupporting
confidence: 93%
“…The overall insertion condition, as summarized by Lund and Stovener's modified scheme [5], was comparable in both groups (Tables 2 and 3). Our findings are consistent with the findings of Lande et al [9], who compared Dexmedetomidine and Fentanyl for LMA insertion and found that Dexmedetomidine resulted in an absolutely relaxed jaw in 96.6% of patients.…”
Section: Discussionsupporting
confidence: 93%
“…Our findings are in accordance with study by Lande SA et al . [5] who compared dexmedetomidine and fentanyl for LMA insertion and reported 96.6% patients having absolutely relaxed jaw with dexmedetomidine. The superiority of dexmedetomidine over fentanyl in providing better jaw relaxation for insertion of the SGAD has been reported by other studies as well.…”
Section: Discussionmentioning
confidence: 99%
“…The superiority of dexmedetomidine over fentanyl in providing better jaw relaxation for insertion of the SGAD has been reported by other studies as well. [561012]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation